ANALYSIS OF SUPERIOR COMMODITIES AND DETERMINATION OF AGROPOLITAN ACTIVITY CENTER IN SANROBONE - Siradjuddin, Irsyadi; Sari, Yuliana; Azizah, Nurul Wafiq (Agricultural Socio-Economics Journal, 2023)
The Takalar Regency Spatial Plan designates the Sanrobone sub-district as an area for the cultivation of food crops, horticultural crops, and plantations. Agriculture in Sanrobone plays a crucial role in fulfilling food needs and driving economic growth in rural areas. The research aims to identify superior commodities, determine the agropolitan activity center, and develop strategies for the agropolitan area in the Sanrobone sub-district. The study was conducted from June to November 2022, covering six villages in the Sanrobone sub-district. The analytical techniques employed include LQ analysis, Shift share analysis, Klassen typology, qualitative descriptive analysis, and SWOT analysis. The research findings reveal that the superior commodity of Sanrobone is Chili Pepper, while prospective commodities are Corn and Paddy, and the lagging commodity is Seagrass. The agropolitan activity center is the main farming town in Banyuanyara, with production centers in the village of Tonasa, and farmer collection towns in Paddinging, Ujung Baji, Lagaruda, and Sanrobone. The recommended strategy is a progressive approach, where empowering farmer groups can enhance the economy, especially in the agricultural sector. Encouraging farmer groups in each village to actively participate in established joint farming groups can boost the potential of food crop agriculture in each village and contribute to the development of the agropolitan area.